Optimization of Amylase Production from B. amyloliquefaciens (MTCC 1270) Using Solid State Fermentation. (11th May 2014) - Saha, Koel; Maity, Sujan; Roy, Sudeshna; Pahan, Koustav; Pathak, Rishija; Majumdar, Susmita; Gupta, Suvroma
Abstract : Demand for microbial amylase production persists because of its immense importance in wide spectrum industries. The present work has been initiated with a goal of optimization of solid state fermentation condition for amylase using agroindustrial waste and microbial strain like B. amyloliquefaciens (MTCC 1270). In an aim to improve the productivity of amylase, fermentation has been carried out in the presence of calcium (Ca +2 ), Nitrate (NO3 − ), and chloride ions (Cl − ) as well as in the presence of D-inositol and mannitol. Amylase needs calcium ion for the preservation of its structure, activity and stability that proves beneficial also for amylase production using solid state fermentation. The inclusion of ions and sugars in the SSF media is promising which can be explained by the protection offered by them against thermal decay of amylase at various incubation periods at 37°C.